Waẓīfah al-Lugah fī al-Kasyf ‘an Anmāṭ al-Ŝaqāfah fī Nījīriyā - Aji, Usman Muhammad (Study Program of Arabic Language Teaching, 2024)
This research aims to describe the main role of language in revealing the cultural patterns of Nigerian-African society. This research is qualitative with a bibliographic type. As literature research, this research uses primary data related to research articles that explain the function of language in intercultural communication in Nigerian-African communities. Data sources were accessed from reputable online e-journals. Data collection techniques are implemented with documentation. Data analysis was carried out using interpretative descriptive techniques. The research results state that language and culture are two of the most important things that determine the personality of individuals and groups and contribute to directing the thinking of the Nigerian-African community, especially in the expansion of cross-cultural speech and communication on the African continent. Language in the socio-cultural context of Nigeria-Africa is one of the impacts of colonialism, which caused Nigeria to have more than 200 regional languages. The Nigerian African community continues to make preventive efforts to preserve regional languages amid continuous disruption and change.